SQSTM1/p62 interacts with HDAC6 and regulates deacetylase activity. - Jin Yan; Michael Lamar Seibenhener; Luis Calderilla-Barbosa; Maria-Theresa Diaz-Meco; Jorge Moscat; Jianxiong Jiang; Marie W Wooten; Michael C Wooten (PLoS ONE, 2013)
Protein aggregates can form in the cytoplasm of the cell and are accumulated at aggresomes localized to the microtubule organizing center (MTOC) where they are subsequently degraded by autophagy. In this process, aggregates are engulfed into autophagosomes which subsequently fuse with lysosomes for protein degradation. A member of the class II histone deacetylase family, histone deacetylase 6(HDAC6) has been shown to be involved in both aggresome formation and the fusion of autophagosomes with lysosomes making it an attractive target to regulate protein aggregation. The scaffolding protein sequestosome 1(SQSTM1)/p62 has also been shown to regulate accumulation and autophagic clearance of protein aggregates. Recent studies have revealed colocalization of HDAC6 and p62 to ubiquitinated mitochondria, as well as, ubiquitinated protein aggregates associated with the E3 ubiquitin ligase TRIM50. HDAC6 deacetylase activity is required for aggresome formation and can be regulated by protein interaction with HDAC6. Due to their colocalization at ubiquitinated protein aggregates, we sought to examine if p62 specifically interacted with HDAC6 and if so, if this interaction had any effect on HDAC6 activity and/or the physiological function of cortactin-F-actin assembly. We succeeded in identifying and mapping the direct interaction between HDAC6 and p62. We further show that this interaction regulates HDAC6 deacetylase activity. Data are presented demonstrating that the absence of p62 results in hyperactivation of HDAC6 and deacetylation of α-tubulin and cortactin. Further, upon induction of protein misfolding we show that p62 is required for perinuclear co-localization of cortactin-F-actin assemblies. Thus, our findings indicate that p62 plays a key role in regulating the recruitment of F-actin network assemblies to the MTOC, a critical cellular function that is required for successful autophagic clearance of protein aggregates.